Roslyn Weiss, Socrates dissatisfied. An Analysis of Plato’s Crito, New York-Oxford, Oxford University Press, 1998, 187 pp. - Santa María, Andrés (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Filosofía., 2003)

(untitled)
Fil: Santa María, Andrés.